IoT-Based Monitoring And Control Of Water Turbidity And Automatic Fish Feeding - Nanda Eka Juniawan; Riska Riska; Yessi Mardiana (Jurnal Media Computer Science, 2026)
The development of Internet of Things (IoT) technology has had a significant impact in various fields, including the fisheries sector. In fish farming, water quality and feeding efficiency are important factors that affect fish health and growth. This study aims to design and implement IoT-based automatic fish feed and water turbidity monitoring system. This system uses an ESP32 microcontroller connected to a turbidity sensor to monitor water turbidity levels, an ultrasonic sensor to detect feed levels, and actuator devices in the form of servos and water pumps. Turbidity data and device status are transmitted in real-time via MQTT protocol to web-based monitoring application and an Android app. Test results indicate that the system can accurately monitor water turbidity levels and activate feeding according to a schedule or manually via the user interface. The testing was conducted in a 40x12x15 cm aquarium containing five guppy ornamental fish, and on the seventh day, an increase of 1 NTU was recorded. The implementation of this technology is expected to improve operational efficiency, reduce feed waste, and maintain aquarium environmental quality sustainably..